Techniques for evaluating digestibility of energy, amino acids, phosphorus, and calcium in feed ingredients for pigs - Zhang, Fengrui (Anim Nutr, 2017)
Sound feed formulation is dependent upon precise evaluation of energy and nutrients values in feed ingredients. Hence the methodology to determine the digestibility of energy and nutrients in feedstuffs should be chosen carefully before conducting experiments. The direct and difference procedures are widely used to determine the digestibility of energy and nutrients in feedstuffs. The direct procedure is normally considered when the test feedstuff can be formulated as the sole source of the component of interest in the test diet. However, in some cases where test ingredients can only be formulated to replace a portion of the basal diet to provide the component of interest, the difference procedure can be applied to get equally robust values. Based on components of interest, ileal digesta or feces can be collected, and different sample collection processes can be used. For example, for amino acids (AA), to avoid the interference of fermentation in the hind gut, ileal digesta samples are collected to determine the ileal digestibility and simple T-cannula and index method are commonly used techniques for AA digestibility analysis. For energy, phosphorus, and calcium, normally fecal samples will be collected to determine the total tract digestibility, and therefore the total collection method is recommended to obtain more accurate estimates. Concerns with the use of apparent digestibility values include different estimated values from different inclusion level and non-additivity in mixtures of feed ingredients. These concerns can be overcome by using standardized digestibility, or true digestibility, by correcting endogenous losses of components from apparent digestibility values. In this review, methodologies used to determine energy and nutrients digestibility in pigs are discussed. It is suggested that the methodology should be carefully selected based on the component of interest, feed ingredients, and available experimental facilities.